Plasmodium vivax circumsporozoite variants and Duffy blood group genotypes in the Brazilian Amazon region - Storti-Melo, Luciane M. [UNESP]; de Souza-Neiras, Wanessa C. [UNESP]; Cassiano, Gustavo C. [UNESP]; Joazeiro, Ana C.P.; Fontes, Cor J.; Bonini-Domingos, Cláudia R. [UNESP]; D'Almeida Couto, Álvaro A.R.; Povoa, Marinete M.; de Mattos, Luiz C. [UNESP]; Cavasini, Carlos E.; Rossit, Andréa R.B. [UNESP]; Machado, Ricardo L.D. [UNESP] (My University, 2009)
The circumsporozoite protein (CSP) of the Plasmodium vivax infective sporozoite is considered to be a major target for the development of recombinant malaria vaccines. The Duffy blood group molecule acts as the red blood cell receptor for P. vivax. We review the frequency of P. vivax CSP variants and report their association with the Duffy blood group genotypes from Brazilian Amazon patients carrying P. vivax malaria. Peripheral blood samples were collected from 155 P. vivax-infected individuals from five Brazilian malaria-endemic areas. The P. vivax CSP variants and the Duffy blood group genotypes were assessed using PCR/RFLP. In single infections, the VK210 variant was the commonest followed by the P. vivax-like variant. The typing of P. vivax indicated that the frequency of variants among the study areas was significantly different from one to another. This is the first detection of the VK247 and P. vivax-like variant in single infections in endemic areas of Brazil. Association of the CSP P. vivax variants with the heterozygous Duffy blood group system genotype was significant for VK210 single infection. These observations provide additional data on the Plasmodium-host interactions concerning the Duffy blood group and P. vivax capability of causing human malaria. © 2008 Royal Society of Tropical Medicine and Hygiene.
Keywords: Brazil; Circumsporozoite protein; Duffy blood group system; Genotype; Malaria; Plasmodium vivax